A miniaturized 35 GHz 65‐nm CMOS digital‐controlled differential variable gain amplifier. Issue 1 (23rd September 2021) - Cheng, Wei‐Chung; Tsai, Zuo‐Min
Abstract: This paper presents a 35 GHz differential variable gain amplifier (VGA) with 4‐bit digital‐controlled gain‐tuning using 65‐nm CMOS process. Using the proposed miniaturized differential matching inductors, a core size of the VGA is only 0.53 × 0.26 mm. The digital gain control mechanism is achieved using the digital version current steering topology. The measured gain control range of the VGA is from 17.4 to 9 dB at 35 GHz with 16 different linear‐in‐dB gain states. Thus, this work achieves the maximum peak gain per unit core size and maintains a much better gain control range per unit core size. The measured root mean square gain error is <0.29 dB and phase error is < 4.6 ° from 34 to 36.5 GHz.